Effects of air pollution on the incidence of myocardial infarction. Issue 21 (26th July 2009) - Bhaskaran, K; Hajat, S; Haines, A; Herrett, E; Wilkinson, P; Smeeth, L
Abstract : Context: Short-term fluctuations in air pollution have been associated with changes in both overall and cardiovascular mortality. Objective: To consider the effects of air pollution on myocardial infarction (MI) risk by systematically reviewing studies looking at this specific outcome. Data sources: Medline, Embase and TOXNET publication databases, as well as reference lists and the websites of relevant public organisations. Study selection: Studies presenting original data with MI as a specific outcome and one or more of the following as an exposure of interest were included: particulate matter (PM), black carbon/black smoke, ozone, carbon monoxide, nitrogen oxides, sulphur dioxide and traffic exposure. Data extraction: The effects of each pollutant on risk of MI, including effect sizes and confidence intervals, were recorded where possible. Methodological details were also extracted including study population, location and setting, ascertainment of MI events, adjustment for potential confounders and consideration of lagged effects. Results: 26 studies were identified: 19 looked at the short-term effects of pollution on a daily timescale; the remaining 7 at longer-term effects. A proportion of studies reported statistically significant detrimental effects of PM with diameter <2.5 µm (3/5 studies, risk increase estimates ranging from 5 to 17% per 10 µg/m 3 increase), PM <10 µm (3/10, 0.7–11% per 10 µg/m 3 ), CO (6/14, 2–4% per ppm), SO2 (6/13, effect estimates on varied scales) and NO2 (6/13, 1–9% per 10 ppb). Increasing ozone levels were associated with a reduction in MI risk in 3/12 studies. A number of differences in location, population and demographics and study methodology between studies were identified that might have affected results. Conclusion: There is some evidence that short-term fluctuations in air pollution affect the risk of MI. However, further studies are needed to clarify the nature of these effects and identify vulnerable populations and individuals.